2016
DOI: 10.1176/appi.ajp.2016.16010025
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Basis for Deficient Excitatory Drive to Cortical Parvalbumin Interneurons in Schizophrenia

Abstract: Objective Deficient excitatory drive to parvalbumin-containing cortical interneurons is proposed to serve as a key neural substrate for altered gamma oscillations and cognitive dysfunction in schizophrenia. However, a pathological entity producing such a deficit has not yet been identified. In this study, we tested the hypothesis that cortical parvalbumin interneurons receive fewer excitatory synaptic inputs in individuals with schizophrenia. Method Fluorescent immunohistochemistry, confocal microscopy and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
122
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 126 publications
(132 citation statements)
references
References 55 publications
9
122
1
Order By: Relevance
“…These results might seem contradictory with prior findings that (i) PV expression is activity dependent (20,38,39), and (ii) the density of excitatory synapses on PV neurons positively predicts PV immunoreactivity levels in mouse hippocampus (44) and human DLPFC (28). However, we also found that the excitatory synapses remaining after pruning have higher apparent levels of VGlut1 and PSD95 proteins.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…These results might seem contradictory with prior findings that (i) PV expression is activity dependent (20,38,39), and (ii) the density of excitatory synapses on PV neurons positively predicts PV immunoreactivity levels in mouse hippocampus (44) and human DLPFC (28). However, we also found that the excitatory synapses remaining after pruning have higher apparent levels of VGlut1 and PSD95 proteins.…”
Section: Discussioncontrasting
confidence: 99%
“…After washing three times in PBS, sections were mounted in Prolong Gold Antifade reagent (Life Technologies) and stored at 4°C until imaging. The specificity of these antibodies has been described previously (28).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations